Factor XIII Deficiency Managed With Individualized Homoeopathic Medicine In Intellectually Disabled Child: An Evidence Based Case Report - Shaikh, Afroz; Kundu, Tapas; Ghosh, Kanjaksha; Kumat, Omkar; Mirza, Gulfisha (Homœopathic Links, 2022)
Factor XIII deficiency is an inherited bleeding disorder, which is rare, ∼1 in 5,000,000, while its combination with an intellectual disability is seldom. It is mostly a result of genetic mutation caused due to consanguineous marriage. Due to deficiency of fibrin stabilising factor, a clot formed is weak and leads to fibrinolysis, which is evident as unstoppable bleeding from umbilical cord stump, epistaxis and bleeding from various organs. The condition is made worst due to intellectual disability as the patient is more prone to injuries due to lack of knowledge of impending dangers. The latest provision of gene therapy is yet to be achieved in such cases and therefore the biggest challenge lies in keeping these patients fit and functional with optimum quality of life. The anxiety of parents is intensified due to the overall condition of the patient. This case report presents homoeopathic management of one such case. The patient was under treatment for almost a decade. Acute homoeopathic medicines efficiently managed acute haemorrhagic episodes. Constitutional medicine Bufo Rana was prescribed in the asymptomatic phase, which helped to reduce the frequency and intensity of bleeding and also helped to improve social quotient of the patient. The social quotient was assessed employing the Vineland Social Maturity Scale, and the result shows that the social quotient of the patient has improved from 8.3 to 41.66. The anxiety of parents also reduced, which was measured using the Family Interview for Stress and Coping in Mental Retardation Scale. The case analysis was done using a paired t-test. The p-value is less than 0.0001 and highly significant. The evaluation of the homoeopathic treatment was done using modified Naranjo criteria for homoeopathy. Homoeopathy medicines efficiently managed the acute episodes of bleeding and also showed improvement in the intellectual disability.
Keywords: case report; consanguineous marriage; factor XIII deficiency; homoeopathy; intellectual disability